PERAN KEPUASAN PELANGGAN MEMEDIASI PENGARUH PENGALAMAN BERWISATA DAN CITRA DESTINASI TERHADAP NIAT BERKUNJUNG KEMBALI (Studi pada Desa Wisata Kertalangu) - Kyana, Ni Luh Gede Sari Marta; Suandari, Ni Putu Khrisnia; Hermarani, Putu Arina; Ekawati, Ni Wayan; Giantari, IGAK (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
The existence of the Kertalangu Tourism Village as a tourist attraction became increasingly visible when the tourism village received the Nusantara Tourism Village Promotion award in 2022. However, it appeared that the lack of care and maintenance causes damage to tourism support facilities. The results of the pre-survey are that most of the respondents intend to return to Kertalangu Tourism Village with influencing factors, namely the feeling of security and the uniqueness of the tourist village, and 83.33 percent of respondents stated that they get what they want when visiting Kertalangu Tourism Village. Data analysis in this study was the SEM application accompanied by the VAF test on 91 respondents. All variable models in direct hypothesis testing obtain positive Path Coefficient values. In the indirect hypothesis, tourist satisfaction has a positive and significant mediating role in the effect of destination image on revisit intention and the effect of tourist experience on revisit intention.